(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Glycosmis pentaphylla (Retz.) DC., commonly known as "orangeberry" or "Ashsheora," is a medicinal plant from the Rutaceae family (Khare et al., 2007). It is widely used in traditional medicine for treating fever, respiratory disorders, skin diseases and inflammation. Phytochemical studies reveal that it contains alkaloids, flavonoids and coumarins with significant antimicrobial, antioxidant and hepatoprotective activities (Samy et al., 2008). The antidiarrheal, analgesic and anti-hyperglycemic properties of Glycosmis pentaphylla (Retz) DC were assessed in this investigation. Methanolic bark extracts of the plant were subjected to various in vivo assays to determine their pharmacological properties by using Swiss albino mice weighing 20–25 grams. G. pentaphylla (Retz.) DC demonstrates remarkable pharmacological activities, including analgesic, antidiarrheal and antihyperglycemic properties, supported by standard experimental data. Analgesic activity was assessed using formalin-induced writhing and hot plate tests in Swiss albino mice. The methanol extract significantly reduced pain responses by 48% compared to the standard diclofenac sodium’s 68% (10 mg/kg). For antidiarrheal activity, the castor oil-induced diarrhea model revealed that the petroleum ether fraction reduced diarrhea frequency by 58% at 200 mg/kg, closely matching the standard loperamide’s (5 mg/kg) 68% efficacy. Additionally, the antihyperglycemic activity was evaluated using the oral glucose tolerance test in diabetic mice, where the methanol extracts reduced blood glucose levels by 25%, nearly equivalent to the standard glibenclamide’s (10 mg/kg) 30%. These findings validate the traditional uses of G. pentaphylla and highlight its potential for therapeutic applications. Bangladesh Pharmaceutical Journal 28(1): 44-48, 2025 (January)